GE_GERICHTE P/10685/2016 vom 11. Oktober 2023 - GE Cour de justice (2023)
PERSONNE MORALE;ORGANE(PERSONNE MORALE);VOL(DROIT PÉNAL);ABUS DE CONFIANCE;GESTION DÉLOYALE;DROIT D'ÊTRE ENTENDU | CPP.319; Cst.29; CP.139; CP.138; CP.143; CP.158